Design of a multimodal (1H/23Na MR/CT) anthropomorphic thorax phantom - Neumann, Wiebke; Schad, Lothar R.; Zöllner, Frank G. (Zeitschrift für medizinische Physik, 2017)
Objectives: This work proposes a modular, anthropomorphic MR and CT thorax phantom that enables the comparison of experimental studies for quantitative evaluation of deformable, multimodal image registration algorithms and realistic multi-nuclear MR imaging techniques. Methods: A human thorax phantom was developed with insertable modules representing lung, liver, ribs and additional tracking spheres. The quality of human tissue mimicking characteristics was evaluated for 1H and 23Na MR as well as CT imaging. The position of landmarks in the lung lobes was tracked during CT image acquisition at several positions during breathing cycles. 1H MR measurements of the liver were repeated after seven months to determine long term stability. Results: The modules possess HU, T1 and T2 values comparable to human tissues (lung module: −756±148HU, artificial ribs: 218±56HU (low CaCO3 concentration) and 339±121 (high CaCO3 concentration), liver module: T1=790±28ms, T2=65±1ms). Motion analysis showed that the landmarks in the lung lobes follow a 3D trajectory similar to human breathing motion. The tracking spheres are well detectable in both CT and MRI. The parameters of the tracking spheres can be adjusted in the following ranges to result in a distinct signal: HU values from 150 to 900HU, T1 relaxation time from 550ms to 2000ms, T2 relaxation time from 40ms to 200ms. Conclusion: The presented anthropomorphic multimodal thorax phantom fulfills the demands of a simple, inexpensive system with interchangeable components. In future, the modular design allows for complementing the present set up with additional modules focusing on specific research targets such as perfusion studies, 23Na MR quantification experiments and an increasing level of complexity for motion studies.
Gesehen am 25.04.2018